Editorial - Iqbal, Badar Alam (Africa Development, 2023)
It is a well-established that the promotion of regional development always results in a higher degree of socioeconomic development, for every country or region, whether they are developed, developing or least-developed economies. African economies are no exception to this rule. This idea is even more valid and more relevant for the ongoing economic and social development (two faces of the same coin) of African economies, where there is greater room for accelerating the pace of growth and development. The role of Africa in the global economy and its contribution has been growing year after year. According to calculations by the African Development Bank (ADB), the growth rate of the aggregate real GDP of African economies was predicted to reach 4.0 per cent in 2019 and 4.1 per cent in 2020. Although these growth rates are still lower than those witnessed by emerging economies, namely China and India, it is believed that African economies will nevertheless exceed the average growth rate in other developing countries and emerging economies.1 To reach their objectives of attaining quantitative development (higher GDP) and qualitative development (improvement in standard of living and quality of life), African states will have to take integrated and systematic measures aimed at solving the persistent and alarming problems of the continent, such as accelerating the pace of development of the economy, trade and the social sector. Major challenges are still faced by African nations, namely poverty, hunger, disease, lack of education, underdeveloped infrastructures (hard and soft), increasing dependence on resource exports, and the influence of foreign monopolies. The emerging economies, especially the non-African BRICS countries (including Brazil, Russia, India, and China), in their turn, have been showing increasing interest in the African region in recent years. At the 2022 BRICS Summit, these nations emphasised the need for and significance of achieving progress through collaboration between developing countries, especially global South cooperation, in terms of trade and investment flow, which is the sine qua non for the acceleration of the pace of growth and development. Two emerging economies—China and India—must play the role of promoters, not rivals. When working for economic and social development for the continent, developed and developing countries must establish backward and forward linkages with African countries. The developed countries of the global North must keep in mind the newly emerging trends of African development, which include the delegation of authority to supranational organisations (the African Union and other regional institutions), ecologically sustainable development of human capital and the infrastructure, formation of the ICT market, development of Big Data and AI, and other equally important processes. Why a Special Issue? The general rule on development highlighted above was recently interrupted by the Covid-19 crisis, a crisis that has had far-reaching and direct impact and implications for African economies, not least because it drastically affected the movement of goods and services, resulting in an unbearable consequences on African businesses and SMEs. To what extent has this affected Africa’s role in the global economy? Keeping in mind the persisting challenges arising out of Covid-19, there was an urgent need to discuss the different issues relating to this pandemic at length. This formed the justification for this issue of Africa Development in which we undertake to examine critical issues that are directly and indirectly related to the impact and implications of Covid-19 on African economies. In all, eleven papers were received. Out of these, seven were selected for inclusion in this special issue. The papers were vigorously peer reviewed by two reviewers to ensure high scientific quality. These seven papers touch on different issues of Covid-19 and African development. But as it has become a tradition in CODESRIA, we also use the pages of this journal to publish the Thandika Mkandawire Annual Memorial Lecture which was prepared separately by Fiona Tregenna and delivered in 2022. The Structure of the Papers The first paper by Felix Fofana N’Zue and Adjoua Math Komenan aims to provide a better understanding of the possible link or interaction between the spread of the Covid-19 pandemic in West Africa, as proxied by the rate of infection, and the state of governance in the ECOWAS countries. The article finds that governance did not significantly impact the Covid-19 infection rate in the ECOWAS region, but tourism and external debt did. The authors then urge development partners to pay close attention to the reliability of Covid-19 confirmed cases to ensure that the data collected is not manipulated for any reasons whatsoever. The second paper, authored by Tope Akinyetun, examines the regional impact of the pandemic on the security and development in the Sahel. The author finds that Covid-19 exacerbated the threat of insecurity in the region due to pre-existing weak governance, poor state capacity, and climate change, which were already worsening and causing more risks and increasing the severity of violent conflicts. The result of this has been further fragility, loss of income, food insecurity, displacement, loss of livelihood, increased poverty, unemployment, hunger, humanitarian crises and contracting economies. ...